Employee experience as a foundation to build superior customer experience : IEC LV Motors, ABB Oy - Patama, Katriina (My University, 2021)
Nowadays great products are not simply enough, rather companies are forced to produce a good service experience in addition to their range of products. Market leadership is universally shift-ing towards organizations, who succeed in creating the best possible customer experience in their field as a part of their business. Dissatisfied customers become costly to companies, both financially and in the form of loss of reputation, when customers switch to a competing company where their needs and desires are better met. Employees of companies are the executors of the company’s result, which is why their treatment is also directly reflected in the company’s cus-tomers. Therefore, employee experience is an important element to invest in when the desire is to create superior customer experience. This study has been conducted in collaboration with ABB as a part of the larger Superior Cus-tomer Experience (SCE) project. The aim of the thesis is to understand and reflect the connection of employee experience and customer experience in order to gain an understanding of the con-nection between these factors. Theoretical background was built to generate understanding of construction and scale of employee experience and psychological contract as well as the for-mation of customer experience and its appearance in business relationships. The study was im-plemented by interviewing employees working at different stages of the customer journey, in order to achieve the most comprehensive and diverse results possible to fully understand the service experience. Semi-structured interviews were held via Teams and in total eleven employ-ees were interviewed. The study identified six key themes, which were recognized to have a massive impact on ongoing business and consequently formulating the connection between employee experience and cus-tomer experience. These themes were identified to represent interaction and response time, workload and work community, skills and training, supervisory work and management, pro-cesses and systems, and tools. Results of the study acknowledged multiple critical points and targets for development, how the customer experience can be taken to a better level by paying attention to the indicated points initiated by employees. Above all, companies are not able to attain a superior customer experience without its most essential link between the company and the customers, its own employees.
Keywords: customer experience; customer service; customer satisfaction; employees; fi=Kansainvälinen liiketoiminta|en=International Business|; Master’s Programme in Strategic Business Development